PENGARUH SERVICE QUALITY TERHADAP CUSTOMER LOYALTY DENGAN CUSTOMER SATISFACTION SEBAGAI VARIABLE MEDIASI (Studi Pada Hotel The Breezes Bali) - I Putu Gede Angga Sugiarsa; Luh Komang Candra Dewi; I Putu Bagus Suthanaya (JUIMA : JURNAL ILMU MANAJEMEN, 2018)
This study discussed the role of service quality in improving customer satisfaction and loyalty of The Breezes Bali. Respondents in this study were 91 respondents with the criteria ever stay at The Breezes Bali hotel more than twice, at least 17 years old. Determination of sample using purposive sampling method. This research used Partial Least Square (PLS) analysis with SmartPLS program. The results showed that: 1) Quality of service had a positive and significant impact on customer satisfaction, 2) Quality of service had a positive but not significant effect to customer loyalty, 3) Satisfaction had a positive and significant impact on customer loyalty, 4) Customer satisfaction able to be a mediation variable shown by the results of service loyalty analysis is able to influence consumer satisfaction and customer satisfaction influence loyalty. The results of this study imply that the management of The Breezes Bali to improve the quality of services with emphasis on reability by serving customers or customers well. Increased customer satisfaction is more emphasis on improving corporate image by maintaining the good name of The Breezes Hotel Bali. Furthermore, customer loyalty can be improved by word of mouth communication to the customer. With word of mouth communication, customers will give positive information about Hotel the breezes Bali to others.